Perspectives on the adherance to scrum rules in software project management - Leanah Alsaber; Ebtesam Al Elsheikh; Sarah Aljumah; Nor Shahida Mohd Jamail (Institute of Advanced Engineering and Science, 2021)
Adapting users need to fulfill their requirements and delivering products to be on time within the planned cost, is critical matter that all software project managers (SPM) put the highest priority for it while considering the users satisfaction at the same time. Agile methodology is one of the solutions provided by software engineers (SE), to get the customers involved in the system development life cycle (SDLC) to avoid the risk nonconformance cost. Yet SPM’s still facing the nonconformance costs and the dynamic changes, and the root cause of the issue is not pointed on to find a solution for it. This undertaking research aimed at determining whether software developers understand scrum rules. In addition, how does this knowledge gab affect the software projects success from the project management perspective. Furthermore, the engagement studied the impact of lack of enough knowledge on the topic to project delivery. The collected data from the qualitative and quantitative methods, which was conducted with scrum teams who worked in the health information system (HIS), Educational solutions, and Governmental solutions has showed deviations in organizational practices and team conflicting, competition, and pressure as well as declined product quality.